2017
DOI: 10.1371/journal.pone.0179854
|View full text |Cite
|
Sign up to set email alerts
|

The cost of demand creation activities and voluntary medical male circumcision targeting school-going adolescents in KwaZulu-Natal, South Africa

Abstract: BackgroundVoluntary medical male circumcision is an integral part of the South African government’s response to the HIV and AIDS epidemic. However, there remains a limited body of economic analysis on the cost of VMMC programming, and the demand creation activities used to mobilize males, especially among adolescent boys in school. This study addresses this gap by presenting the costs of a VMMC program which adopted two demand creation strategies targeting school-going males in South Africa.MethodsCost data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Eleven studies presented cost data [14,25,[36][37][38][39][40][41][42][43][44], three of which were related to articles included in the main effectiveness review. Studies were published between 2012 and 2018 and took place in Kenya [38,41], South Africa [39,42,43], Tanzania [44], Uganda [36,37,40], and Zimbabwe [14,25]. Descriptions of included cost studies and their outcomes are presented in Table 5.…”
Section: Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies presented cost data [14,25,[36][37][38][39][40][41][42][43][44], three of which were related to articles included in the main effectiveness review. Studies were published between 2012 and 2018 and took place in Kenya [38,41], South Africa [39,42,43], Tanzania [44], Uganda [36,37,40], and Zimbabwe [14,25]. Descriptions of included cost studies and their outcomes are presented in Table 5.…”
Section: Costsmentioning
confidence: 99%
“…Descriptions of included cost studies and their outcomes are presented in Table 5. Seven of the included studies assessed community-based interventions [14,36,[40][41][42][43][44], two assessed school-based interventions [25,39], and two assessed facility-based interventions [37,38]. Generally, cost studies showed that service delivery interventions may create economies of scale and efficiencies when implemented widely.…”
Section: Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates from the sensitivity analyses indicate that the VMMC intervention is highly cost-effective when administered to street-connected youth, even at a cost of $108 per individual, and these estimates are in line with previous findings from the literature [ 20 , 23 , 32 ]. While differentiated approaches have shown encouraging results for developing VMMC programs that target adolescents [ 29 31 ], they often incur greater costs to reach this age group and are limited to the local context [ 47 ]. Findings from this pilot intervention are consistent with studies modelling age-specific VMMC programs in Sub-Saharan Africa [ 23 25 ] and may support, from a cost-effectiveness perspective, spending more on the differentiated approaches needed to reach these populations.…”
Section: Discussionmentioning
confidence: 99%
“…The strategies Kenya has used to achieve the national target of circumcising 80% of the country’s adult males [ 27 ] have routinely overlooked SCY who do not access health services through traditional channels [ 27 , 28 ]. Programs which employ innovative and locally-tailored approaches to youth and hard-to-reach populations have shown higher circumcision rates, more efficient resource utilization and increased cost-savings [ 29 32 ].…”
Section: Introductionmentioning
confidence: 99%